2003
DOI: 10.1007/s00535-003-1201-0
|View full text |Cite
|
Sign up to set email alerts
|

Patients with severe liver cirrhosis followed up by L-[1- 13 C] phenylalanine breath test

Abstract: Compared to healthy subjects, patients with severe liver cirrhosis (LC) are reported to show lower values in the L-[1-(13)C] phenylalanine breath test (PBT). We performed this test several times during the clinical course in two patients with severe liver cirrhosis (LC). Patient 1 was a 67-year-old woman with non-B, non-C LC and hepatocellular carcinoma (HCC) in the lateral hepatic segment. Because the patient wanted to receive nonsurgical treatment for HCC, intraarterial administration of zinostatin stimalame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…They found that 13 CO 2 excretion decreased by up to 80% after intake of l-[1-13 C] phenylalanine ( 13 C-Phe). Similar results were subsequently obtained in different populations by other researchers (Tugtekin et al, 1999;Lara Baruque et al, 2000;Kobayashi et al, 2001;Ishii et al, 2003a;Festi et al, 2005). Our clinical research has also supported the clinical value of PheBTs Sun et al, 2003).…”
supporting
confidence: 94%
See 1 more Smart Citation
“…They found that 13 CO 2 excretion decreased by up to 80% after intake of l-[1-13 C] phenylalanine ( 13 C-Phe). Similar results were subsequently obtained in different populations by other researchers (Tugtekin et al, 1999;Lara Baruque et al, 2000;Kobayashi et al, 2001;Ishii et al, 2003a;Festi et al, 2005). Our clinical research has also supported the clinical value of PheBTs Sun et al, 2003).…”
supporting
confidence: 94%
“…Studies have.found that after intravenous administration of phenylalanine to patients with liver diseases, decreased elimination was consistent with a loss in tyrosine production (Matthews et al, 1993), and that the phenylalaine elimination rate in the central vein was highly correlated with the total amino acid elimination rate (Levine and Conn, 1967). Many researchers (Burke et al, 1997;Tugtekin et al, 1999;Lara Baruque et al, 2000;Kobayashi et al, 2001;Ishii et al, 2003a;Festi et al, 2005;Yan et al, 2003;Sun et al, 2003) have independently evaluated hepatocyte function and liver functional reserve by PheBTs, and found that breath test parameter levels were reduced. The extent of this decrease was somewhat correlated with many blood biochemical indices and the results of Indocyanine Green (ICG) examination.…”
Section: Indexmentioning
confidence: 92%
“…Liver injury can cause a lower rate of phenylalanine metabolism (and uptake) and consequently the increase of serum phenylalanine concentration [4]. Some studies indicated that 13 C-phenylalanine breath test could be useful for determination of liver function [5][6][7]. Nonalcoholic fatty liver disease (NAFLD) represents different clinical conditions characterized histologically by an excessive accumulation of fat in the liver of subjects not consuming alcohol or consuming minimal amount of ethanol [8].…”
Section: Introductionmentioning
confidence: 99%
“…With respect to 13 C breath tests for cytosol, the usefulness of the l-[1-13 C]phenylalanine breath test (PBT) [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] and [ 13 C]galactose breath test [26][27][28][29][30][31] has been reported. Several studies focusing on mitochondria indicated the usefulness of the α-ketoisocaproate breath test [32][33][34][35][36][37][38] and methionine breath test (MethioBT) [39][40][41][42][43][44][45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%